Evaluation of membrane anaerobic system (MAS) for palm oil mill effluent (POME) treatment - Hua Chyn, Lee (2012)
The direct discharge of Palm Oil Mill Effluent(POME)into river causes serious environmental pollutions due to its high content of organic matter which causes depletion of oxygen in water bodies.The conventional anaerobic POME treatment by using anaerobic ponding system requires longer Hydraulic Retention Time (HRT) and large space.In this study,the efficiency of Membrane Anaerobic System (MAS) in treating POME was investigated.The MAS is a system that consists of an anaerobic digester,a centrifugal pump and Cross-Flow Ultrafiltration (CUF) Membrane with Molecular Weight Cut-off (MWCO) 200 kDa which have been operated at the pressure of 1.5 bars to 2 bars.Three runs of the experiment had been done on three kinds of the POME samples, 50 % diluted raw POME (Run 1),anaerobic digested POME without addition of mixed culture inoculum (Run 2) and anaerobic digested POME with addition of mixed culture inoculum (Run 3).Throughout the study,the MAS system was performing better in treating anaerobic digested POME in term of overall Chemical Oxygen Demand (COD) removal efficiency in Run 2 and Run 3 compared to Run 1,which overall COD removal efficiency were 83.94 % (Run 2) and 77.98 % (Run 3).The overall Total Suspended Solid (TSS) removal efficiencies of MAS on POME were varied between 81.02 % and 99.95 % in three runs of the experiments.The overall Volatile Suspended Solid (VSS) removal efficiency of MAS on POME treatment was varied between 74.66 % and 87.87 %.The methane gas production was 80.79 %, 80 % and 78.26 % for Run 1, 2, 3 respectively.The addition of inoculum did not show any significant effect on methane production in Run 3.The methane gas production in MAS through anaerobic digestion of POME was found to be linearly in relationship with the VSS removal efficiency and organic loading.